The role of social actors in building sustainable cities in the Global South - Mvuyana, Bongekile Yvonne Charlotte (Frontiers in Sustainable Cities, 2025)
IntroductionPublic sector institutions must utilize public policies effectively to deliver essential programs and services designed to tackle pressing community issues. The pervasive housing shortages have created significant distress surrounding asset acquisition, housing finance, property dynamics, affordable housing, and community development.MethodologyAdopting a qualitative methodology, the paper using the systematic review rigorously analysed the contributions of social actors in fostering sustainable communities and elevating the living standards of residents. The PRISMA assisted in identifying sources that can be included or excluded in the study for relevance, credibility, and methodological rigor. This diligent search encompassed literature published between 2005 and 2024, using academic databases, including EBSCO, SCOPUS, Google Scholar, Web of Science, ProQuest, Springer, and Science Direct. Furthermore, the inclusion of grey literature and registry sources enriched the inquiry with diverse conceptual perspectives.ResultsA total of 113 records emerged 80 from databases, 20 from registers, and 13 from additional sources like manual searches and unpublished materials. Leveraging social identity theory highlights the importance of individual identification with collective groups that share common interests. The findings unequivocally indicate that robust mechanisms are necessary to allow individuals in need of housing to align themselves with policy concerned groups devoted to building sustainable cities and enriching citizens’ quality of life.DiscussionThis paper decisively assesses the critical role of social actors in constructing sustainable cities that aim to enhance the quality of life for marginalized communities. Active participation in public policy processes is not just beneficial but essential for these community members, enabling them to secure improvements that would be unattainable without their engaged involvement. The paper strongly recommends that social actors engaged in housing challenges take the initiative to advocate for legislative changes that unequivocally benefit their constituents with shared goals.